Hessian fly, Mayetiola destructor (Diptera: Cecidomyiidae), smart-trap design and deployment strategies - Schmid, Ryan B. (Kansas State University, 2018)
Timely enactment of insect pest management and incursion mitigation protocols requires development of time-sensitive monitoring approaches. Numerous passive monitoring methods exist (e.g., insect traps), which offer an efficient solution to monitoring for pests across large geographic regions. However, given the number of different monitoring tools, from specific (e.g., pheromone lures) to general (e.g., sticky cards), there is a need to develop protocols for deploying methods to effectively and efficiently monitor for a multitude of potential pests. The non-random movement of the Hessian fly, Mayetiola destructor (Say) (Diptera: Cecidomyiidae), toward several visual, chemical, and tactile cues, makes it a suitable study organism to examine new sensor technologies and deployment strategies that can be tailored for monitoring specific pests. Therefore, the objective was to understand Hessian fly behavior toward new sensor technologies (i.e., light emitting diodes (LEDs) and laser displays) to develop monitoring and deployment strategies. A series of laboratory experiments and trials were conducted to understand how the Hessian fly reacts to the technologies and how environmental factors may affect the insect’s response. Hessian fly pupae distribution within commercial wheat fields was also analyzed to determine deployment of monitoring strategies. Laboratory experiments demonstrated Hessian fly attraction to green spectrum (502 and 525 nm) light (LEDs), that response increased with light intensity (16 W/m²), and that they responded in the presence of wheat odor and the Hessian fly female sex-pheromone, but, response was reduced under ambient light. These laboratory experiments can be used to build a more targeted approach for Hessian fly monitoring by utilizing the appropriate light wavelength and intensity with pheromone and wheat odor to attract both sexes, and mitigating exposure to ambient light. Together this information suggested that light could be used with natural cues to increase attraction. Therefore, a light source (green laser display) was applied to a wheat microcosm, which resulted in greater oviposition in wheat covered by the laser display. Examination of Hessian fly pupal distribution within commercial wheat fields showed that proportion of wheat within a 1 km buffer of the field affected distribution between fields. This helps to inform deployment of monitoring strategies as it identified fields with a lower proportion of wheat within a 1 km buffer to be at higher risk Hessian fly infestation, and therefore monitoring efforts should be focused on those fields. Together this work demonstrates Hessian fly behavior toward new sensor technologies, how those technologies interact with environmental cues, and how environmental composition affects pupal distribution. Collectively this information will enable cheaper, more accurate and more efficient monitoring of this destructive pest.
Keywords: Hessian fly; Mayetiola destructor; Insect behavior; Insect monitoring; Integrated pest management (IPM); Wheat pest management